The promising role of risk scoring system for Cushing syndrome: Time to reconsider current screening recommendations - Lam-Chung, CE.; Cuevas-Ramos, D. (Frontiers in Endocrinology, 2022)
Despite the current screening approach for Cushing syndrome (CS), delayed diagnosis is common due to broad spectrum of presentation, poor discriminant symptoms featured in diabetes and obesity, and low clinical index of suspicion. Even if initial tests are recommended to screen CS, divergent results are not infrequent. As global prevalence of type 2 diabetes and obesity increases, CS may not be frequent enough to back routine screening to avoid false-positive results. This represents a greater challenge in countries with limited health resources. The development of indexes incorporates clinical features and biochemical data that are largely used to provide a tool to predict the presence of disease. In clinical endocrinology, indexes have been used in Graves’ ophthalmology, hirsutism, and hypothyroidism. The use of clinical risk scoring system may assist clinicians in discriminating CS in the context of at-risk populations and, thus, may provide a potential intervention to decrease time to diagnosis. Development and validation of clinical model to estimate pre-test probability of CS in different geographic source population may help to establish regional prediction model for CS. Here, we review on the latest progress in clinical risk scoring system for CS and attempt to raise awareness for the use, validation, and/or development of clinical risk scores in CS.